Evaluation of data quality in the Spanish EURECCA Esophagogastric Cancer Registry. Issue 12 (December 2021) - Cero, M. Dal; Rodríguez-Santiago, J.; Miró, M.; Castro, S.; Miranda, C.; Santamaría, M.; Gobbini, Y.; Garsot, E.; Pujadas, M.; Luna, A.; Momblán, D.; Balagué, C.; et al.
Abstract: Background: Although the number of nationwide clinical registries in upper gastrointestinal cancer is increasing, few of them perform regular clinical audits. The Spanish EURECCA Esophagogastric Cancer Registry (SEEGCR) was launched in 2013. The aim of this study was to assess the reliability of the data in terms of completeness and accuracy. Methods: Patients who were registered (2014–2017) in the online SEEGCR and underwent esophagectomy or gastrectomy with curative intent were selected for auditing. Independent teams of surgeons visited each center between July 2018 and December 2019 and checked the reliability of data entered into the registry. Completeness was established by comparing the cases reported in the registry with those provided by the Medical Documentation Service of each center. Twenty percent of randomly selected cases per hospital were checked during on-site visits for testing the accuracy of data (27 items per patient file). Correlation between the quality of the data and the hospital volume was also assessed. Results: Some 1839 patients from 19 centers were included in the registry. The mean completeness rate in the whole series was 97.8% (range 82.8–100%). For the accuracy, 462 (25.1%) cases were checked. Out of 12, 312 items, 10, 905 were available for verification, resulting in a perfect agreement of 95% (87.1–98.7%). There were 509 (4.7%) incorrect and 35 (0.3%) missing entries. No correlation between hospital volume and the rate of completeness and accuracy was observed. Conclusions: Our results indicate that the SEEGCR contains reliable data.